2022
DOI: 10.1038/s41598-022-06313-5
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and antioxidant activity of fruit harvested from eight jujube (Ziziphus jujuba Mill.) cultivars at different development stages

Abstract: Jujube is a crop highly resistant to drought and salinity, making it one of the main fruit trees in Xinjiang. The present study evaluated the changes in the physicochemical and antioxidant activities of jujube fruit of eight different cultivars from Xinjiang, China. The developmental stages were selected according to the days after full bloom and fruit peel colour during ripening; these stages included young (S1), fruit core-hardening (S2), green ripening (S3), half-red maturity (S4) and complete red. In prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
6
8
0
Order By: Relevance
“…The decreasing trend observed in total acidity in mulberry cultivars is in line with the outcomes of previous studies [20,21,[42][43][44][45][46][47][48][49][50][51][52][53] considering acidity as a crucial indicator for the determination of fruit quality [54]. The levels of organic acids are usually inversely related to sugar levels during fruit development where sugars accumulate due to sugar import or starch degradation, while organic acids strongly decrease which accumulated in the young fruits [55].…”
Section: Total Acidity (%) In Mulberry Cultivarssupporting
confidence: 89%
See 1 more Smart Citation
“…The decreasing trend observed in total acidity in mulberry cultivars is in line with the outcomes of previous studies [20,21,[42][43][44][45][46][47][48][49][50][51][52][53] considering acidity as a crucial indicator for the determination of fruit quality [54]. The levels of organic acids are usually inversely related to sugar levels during fruit development where sugars accumulate due to sugar import or starch degradation, while organic acids strongly decrease which accumulated in the young fruits [55].…”
Section: Total Acidity (%) In Mulberry Cultivarssupporting
confidence: 89%
“…This increased antioxidant activity of black mulberry cultivars could be associated due to the increased TFC and anthocyanin contents in black cultivars as compared to the white ones. These results supports the outcomes of Saeed et al [20,21], Yongram et al [63] and Arfan et al [76] where the jamun, phalsa and black/purple mulberry fruits during maturation also exhibited the strongest antioxidant activity in DPPH assay while the outcomes are not in agreement with the ndings of Yan et al [52] where the antioxidant activity in jujube fruit was found to decrease with increasing maturity.…”
Section: Antioxidant Activity Of Mulberry Cultivarssupporting
confidence: 82%
“…The total content of jujube gradually decreased during the S2–S6 stage. Minyan 44 et al also discovered that the titrable acid content of jujube decreased with maturity during the jujube growing phase. As a result, jujube was sweeter and less sour after delayed harvesting, which explains why we selected it as the main raw material for Xinjiang dried fruit processing.…”
Section: Resultsmentioning
confidence: 96%
“…[ 6 ] Moreover, the jujube fruit is rich in many nutrients and bioactive substances, including polysaccharides, fatty acids, polyphenols, dietary fiber, nucleotides, and alkaloids. [ 6 ] These nutrients and bioactive substances play important anticancer, [ 7 ] anti‐inflammatory, [ 8 ] antioxidant, [ 9 ] antibacterial, [ 10 ] and antiviral roles. [ 11 ] The typical daily consumption of polyphenols in the human diet amounts to more than 1 g day −1 , and its concentration in the digestive system can reach up to hundreds of micromoles.…”
Section: Introductionmentioning
confidence: 99%